Nanobiossensor a fibra óptica revestido com filme fino de ouro para detecção da bactéria Escherichia coli - Arcas, Ariadny da Silva (2017)
Escherichia coli (E. coli) is a bacterial type that inhabits the intestinal tract of humans and animals, therefore, its presence in water and food is used as indicator of fecal contamination. Depending on the species, it can be harmful to health if ingested. The main method for this microorganism detection is the bacterial culture medium that is timeconsuming and requires a laboratory with specialized personnel. Others sophisticated methods are still not fast enough because they require to send samples to the laboratory and have a high cost of analysis. This work presents the development of a fiber-optic sensor coated with gold thin film for E. coli detection in water as a portable, fast response and low-cost alternative to conventional methodologies. The sensor is manufactured in U-shaped plastic optical fiber (POF) and works by intensity modulation principle excited by a monochromatic light. The light absorption is imposed by two effects: bending loss by refraction and Surface Plasmon Resonance (SPR). Bacterial selectivity was obtained by specific antibodies immobilization on the fiber surface. Sensors coated with several thicknesses of gold thin film were tested in order to improve bacteria adhesion and to enable SPR effect. The sensor showed a detection limit of 1,5 x 103 CFU/mL of E. coli bacteria concentration, demonstrating that the technology might be an efficient tool for quality analysis of water and food.